Beginning SharePoint 2013: building business solutions - Perran, Amanda; Perran, Shane; Mason, Jennifer; Rogers, Laura (Wrox Programmer to Programmer, 2013)
Learn to build business solutions with SharePoint 2013 Now in its third edition, this perennial bestseller features a complete overhaul for the latest version of SharePoint. A must-have for building business solutions in SharePoint, real-world scenarios address critical information management problems and detailed descriptions explain how to efficiently and successfully handle these challenges. Plus, best practices for configuration and customization round out the coverage of getting started with SharePoint 2013 so that you can confidently make this platform work for your business today. Examines product functionality alongside realistic scenarios to provide you with contextual relevance Addresses managing permissions, reporting in SharePoint, and working with access services Offers updated content on working with lists, libraries, workflow, content types, and web parts Reviews social features, forms management, business connectivity services, and more Beginning SharePoint 2013 is an ideal introduction to the latest iteration of this popular content management provider.